TRANSMISI, SANAD KEILMUAN, DAN RESEPSI HADIS PUASA DALÄâ€™IL AL-KHAIRÄT - Rafi?i , Melati Ismaila; Qudsy, Saifuddin Zuhri (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2020)
Dala>il al-Khairat is a kind of fasting that has been practiced by santris in Central and East Java for years. They must be able to pass an ongoing fasting for one or three years, and uniquely, it becomes a happiness for santris to practice it. This paper departs from questions on how this practice is carried out, how the transmission of knowledge come from and how the foundation of the sacred text (such as Hadith) lie behind the practice as the legitimacy of this practice. By using historical method the authors conclude that the practice of Dala>il cannot be separated from the role of Shaykh Yasin Bareng in Kudus who taught the later generations and his students through the process of ija>zah. In addition, we found that the transmission of knowledge about recitation of Dala>il al-Khaira>t was also found in Shaykh Mahfudz at-Tirmasi, one of Muslim scholars who taught at Haramain in XX Century.